Sick of your colleagues' absence? - Patrik Hesselius; Per Johansson; Peter Nilsson (Institute for the Study of Labor (IZA), 2009)
We utilize a large-scale randomized social experiment to identify how coworkers affect each other's effort as measured by work absence. The experiment altered the work absence incentives for half of all employees living in Göteborg, Sweden. Using administrative data we are able to recover the treatment status of all workers in more than 3,000 workplaces. We first document that employees in workplaces with a high proportion treated coworkers increase their own absence level significantly. We then examine the heterogeneity of the treatment effect in order to explore what mechanisms are underlying the peer effect. While a strong effect of having a high proportion of treated coworkers is found for the nontreated workers, no significant effects are found for the treated workers. These results suggest that pure altruistic social preferences can be ruled out as the main motivator for the behaviour of a nonnegligible proportion of the employees in our sample.
urn:nbn:de:101:1-20090209305
Keywords: J24; 330; Social interactions; employer employee data; work absence; fairness; reciprocal preferences; Fehlzeit; Dauer; Soziale Norm; Krankheit; Test; Schweden